2018
DOI: 10.5435/jaaos-d-17-00410
|View full text |Cite
|
Sign up to set email alerts
|

Current Concepts in Orthopaedic Care Disparities

Abstract: Healthcare delivery is profoundly affected by race/ethnicity, sex, and socioeconomic status. The effect of these factors on patient health and the quality of care received is being studied in more detail. Orthopaedic surgery over the past several years has paid increasing attention to these disparities as well. Not only do these disparities exist with regard to accessing care but also with regard to the quality of care received and postoperative outcomes. Total joint arthroplasty, hip fractures, and spine surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 43 publications
1
68
0
Order By: Relevance
“…[1][2][3] Despite increasing utilization of total shoulder arthroplasty (TSA) as an effective management of various shoulder pathologies, [4][5][6] the literature has demonstrated that enduring racial and gender disparities exist in joint replacement procedures. [7][8][9][10][11][12][13][14][15] An 18-year analysis of Medicare part A data showed that in 1991, the use of primary total knee arthroplasty (TKA) was 36% lower for African-Americans compared with Caucasians. 1 Though utilization more than doubled for both African-Americans and Caucasians by 2008, the usage of primary TKA was still 40% lower for African-Americans.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Despite increasing utilization of total shoulder arthroplasty (TSA) as an effective management of various shoulder pathologies, [4][5][6] the literature has demonstrated that enduring racial and gender disparities exist in joint replacement procedures. [7][8][9][10][11][12][13][14][15] An 18-year analysis of Medicare part A data showed that in 1991, the use of primary total knee arthroplasty (TKA) was 36% lower for African-Americans compared with Caucasians. 1 Though utilization more than doubled for both African-Americans and Caucasians by 2008, the usage of primary TKA was still 40% lower for African-Americans.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these studies suggest that those without insurance or with Medicaid are less likely to use health care and are subject to differences in management and poorer outcomes when they do. 2,7,21,24,30,33 Looking specifically at orthoses, government-insured patients have been shown to experience delays up to 3 months in receiving prescribed orthoses compared to private-insured patients. 24 Our study suggests that these patients may not only experience delays but may not receive their orthoses at all.…”
Section: Discussionmentioning
confidence: 99%
“…While large, systematic change will be necessary, strategies can be employed by those working directly in patient care. Pandya et al 21 suggested informing primary care practices of their ability to see patients with limited insurance, limiting blanket refusal policies for government insurance, and educating office staff on how to most efficiently work with Medicare and Medicaid. In regards to race, at least 1 study has shown a low level of recognition of racial disparities in musculoskeletal care by orthopedic surgeons, suggesting a need to raise more awareness of such disparities within the field.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 40 , 42 Ultimately, these discordances in race between providers and patients negatively influence how treatments are administered and subsequent health outcomes across a number of fields. 3 , 9 , 12 , 20 , 21 , 31 , 49 For example, using national Medicare claims data, Skinner et al 43 showed that Black men and Asian women were significantly less likely to receive a clinically warranted total knee arthroplasty, even after controlling for income. Dy et al 11 studied the records of 197,290 patients in New York who underwent surgery for hip fracture and found that Black patients were at significantly greater risk for delayed surgery, reoperation, readmission, and 1-year in-hospital mortality than White patients.…”
mentioning
confidence: 99%